INSTITUTIONAL APPROACHES TO NATIONAL CURRENCY STABILITY: THE ROLE OF GOVERNANCE AND REPUTATION (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article explores the institutional determinants of currency stability, moving beyond the traditional monetarist focus on supply and demand. It examines how Central Bank Independence (CBI), the Rule of Law, and the quality of regulatory frameworks serve as the "soft infrastructure" for currency value. The study analyzes the "Credibility Gap" and demonstrates that institutional transparency reduces the risk premium associated with national currencies. The paper concludes that for emerging economies, institutional reform is as critical to exchange rate stability as technical monetary intervention.
Keywords: Institutional Economics, Central Bank Independence (CBI), Rule of Law, Monetary Credibility, Governance Quality, Currency Stability, New Institutional Economics (NIE), Transaction Costs.